2020
DOI: 10.3390/ijms21072367
|View full text |Cite
|
Sign up to set email alerts
|

Modern Aspects of Immunotherapy with Checkpoint Inhibitors in Melanoma

Abstract: Although melanoma is one of the most immunogenic tumors, it has an ability to evade anti-tumor immune responses by exploiting tolerance mechanisms, including negative immune checkpoint molecules. The most extensively studied checkpoints represent cytotoxic T lymphocyte-associated protein-4 (CTLA-4) and programmed cell death protein 1 (PD-1). Immune checkpoint inhibitors (ICI), which were broadly applied for melanoma treatment in the past decade, can unleash anti-tumor immune responses and result in melanoma re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 148 publications
0
30
0
Order By: Relevance
“…Modern advances in immunotherapy have shifted the treatment approach for multiple solid tumors. Immunotherapy is now the first-line treatment for metastatic melanoma, renal cell carcinoma, and lung cancer [ 17 19 ]. In March 2019, a new combination therapy composed of the anti-PD-L1 antibody atezolizumab and protein-bound paclitaxel received full Food and Drug Administration approval for patients with mTNBC.…”
Section: Discussionmentioning
confidence: 99%
“…Modern advances in immunotherapy have shifted the treatment approach for multiple solid tumors. Immunotherapy is now the first-line treatment for metastatic melanoma, renal cell carcinoma, and lung cancer [ 17 19 ]. In March 2019, a new combination therapy composed of the anti-PD-L1 antibody atezolizumab and protein-bound paclitaxel received full Food and Drug Administration approval for patients with mTNBC.…”
Section: Discussionmentioning
confidence: 99%
“…ECM remodeling is also promoted by FAP, a member of the serine protease family, overexpressed by activated fibroblasts ( Figure 3 ) [ 94 , 95 ]. FAP is also thought to suppress T cell recruitment and function and, therefore, support melanoma immune escape [ 96 , 97 ]. Moreover, it was confirmed that the loss of β-catenin expression in CAFs correlates with a decrease in fibronectin and collagen levels in the tumor stroma.…”
Section: Cancer-associated Fibroblastsmentioning
confidence: 99%
“…Furthermore, a substantial fraction of long-term survivors seems to remain disease-free even after discountinuation of treatment. In fact, ICI-based immunotherapy is approved by the FDA as a standard treatment for patients with advanced or recurrent melanoma [ 116 , 117 , 118 ].…”
Section: Potential Role Of Icis In Rare Vulvar Tumor Typesmentioning
confidence: 99%